Matrix Trays: From waste to opportunities. (1st June 2021) - Ali, Ahmed K.; Layton, Astrid; Kio, Patricia; Williams, Jewel
Abstract: Matrix Trays are single-use plastic carriers used to transport integrated chips and circuit board components during automated test and assembly processes for Printed Circuit Boards. These trays represent a significant yet consistent waste stream; primarily in the electronics industry and many other industries that integrate microchips into their products especially the automotive industry. By the end of 2017, the National Sword Policy which was implemented by China on plastic waste import from other countries and especially the United States catalyzed a huge crisis and forced manufacturers and companies to deal with their own plastic waste streams. This study presents two alternative approaches of reusing trays to the reduced conventional recycling practices which have caused used trays to remain in storage or be deposited in landfills. Approaches including a students' design competition and a proof of concept case study for an autonomous shading device are presented. The shading device was designed, tested and validated. Trays were transformed from waste into 13 possible products showing that a circular economy and industrial symbiosis can be achieved by integrating multidisciplinary reuse approaches for by-product reuse and sustainable industry practices. Environmental and economic impacts were evaluated comparing reuse to recycling, combustion and landfilling. The results showed that reusing trays reduces energy consumption and greenhouse gas emissions. Highlights: Single-use plastic matrix trays transport chips for Printed Circuit Boards. Matrix trays are a significant, consistent waste stream from microchipped products. Chinese National Sword Policy changed matrix tray recycling to landfilling/storage. Circular Economy approaches reduce environmental impacts from used matrix trays. Design/testing/validation of a Circular Economy motivated autonomous shading device.